2022
DOI: 10.1007/s10163-022-01494-7
|View full text |Cite
|
Sign up to set email alerts
|

Household disposal of pharmaceuticals: attitudes and risk perception in a UK sample

Abstract: Pharmaceuticals can enter the environment through disposal in toilets, sinks and general waste. In the UK, household medicines are correctly disposed of by returning them to a pharmacy. This study examined household patterns of medicine waste, storage and disposal practices via a cross-sectional survey with 663 UK adults. Multiple regression was used to explore the contribution of key variables on self-reported medicines disposal behaviour. Analysis demonstrated that age, information, awareness, probability, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
6
1
Order By: Relevance
“…However, in the area of behaviors associated with reducing medication waste, very few studies have employed the TPB or extended TPB to investigate intentions to reduce medication waste (e.g., refs. [ 34 , 38 , 39 , 43 ]). Regardless, according to the results of most of these studies, TPB better predicts waste reduction intentions or behavior.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the area of behaviors associated with reducing medication waste, very few studies have employed the TPB or extended TPB to investigate intentions to reduce medication waste (e.g., refs. [ 34 , 38 , 39 , 43 ]). Regardless, according to the results of most of these studies, TPB better predicts waste reduction intentions or behavior.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Despite it all, current research has focused on investigating issues related to the medication waste reality, such as the examination of medication waste volume [ 2 ], medication waste disposal [ 6 , 9 , 12 , 16 , 17 , 33 , 34 ], medication waste practices [ 13 , 27 ], knowledge, awareness, and attitudes towards wasting medications [ 1 , 28 , 35 ], causative factors of medication waste [ 14 ], and determinants of medications storage [ 5 , 36 , 37 ]. Moreover, other studies have focused on medication waste management [ 4 , 8 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unused or expired pharmaceuticals that are inappropriately disposed of in general waste, poured into a sink, or flushed down toilets can play a role in the spread of AMR [ 39 , 40 ]. A study assessing attitudes to household disposal of pharmaceuticals in the UK found that households where children live more frequently dispose of medications in the bin, sink, or toilet due to perceived risk of danger from accidental ingestion.…”
Section: Four Key Principles Of Sustainable Healthcarementioning
confidence: 99%
“…A study assessing attitudes to household disposal of pharmaceuticals in the UK found that households where children live more frequently dispose of medications in the bin, sink, or toilet due to perceived risk of danger from accidental ingestion. Formulations of pharmaceuticals affected the most common route of disposal (liquid drugs were more frequently poured down the sink rather than put in the bin) [ 40 ]. Infection specialists can increase public awareness to change behaviors at the domestic and individual level, meanwhile recognition and prioritization of AMS and environmental sustainability by health system leaders is necessary to drive changes in how hospital waste is managed.…”
Section: Four Key Principles Of Sustainable Healthcarementioning
confidence: 99%